2009
DOI: 10.1016/j.vetpar.2009.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal nematode infection in beef cattle of different genetic groups in Brazil

Abstract: Resistance to natural infection by gastrointestinal nematodes was compared in 67 female calves of the following genetic groups: Nelore (NX); 1/2 Senepol+1/2 Nelore (SN); and 1/2 Aberdeen Angus+1/2 Nelore (AN). The NX (n=26), SN (n=23) and AN (n=18) animals were monitored for 14 months, during which they remained without treatment, allowed to graze in a tropical environment. Eggs per gram of feces (EPG), coprocultures and packed cell volume (PCV) were carried out monthly. No significant effects of the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 19 publications
2
26
0
5
Order By: Relevance
“…Although it has been shown that cattle with diverse genetics vary in their susceptibility to GIN (Oliveira et al, 2009(Oliveira et al, , 2013, which could be mediated via immunity to GIN (Forbes et al, 2008) there is little evidence associating the variation in productivity with differences in resistance to GIN. The lack of such evidence hinders the incorporation of such traits in breeding indices in cattle and the use of crossbreeding as means of improving performance and disease resistance into cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been shown that cattle with diverse genetics vary in their susceptibility to GIN (Oliveira et al, 2009(Oliveira et al, , 2013, which could be mediated via immunity to GIN (Forbes et al, 2008) there is little evidence associating the variation in productivity with differences in resistance to GIN. The lack of such evidence hinders the incorporation of such traits in breeding indices in cattle and the use of crossbreeding as means of improving performance and disease resistance into cattle.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the emergence of resistance and the presence of residues in meat and milk, it has become necessary to develop alternative control methods (OLIVEIRA et al, 2009). Among these methods is the use of parasitological techniques to identify susceptible animals and thus allow selective application of anthelmintics or even replacement of such susceptible animals within a herd (VERCRUYSSE et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Two generations of crosses produced 229 F2 animals at Embrapa Caprinos e Ovinos (Sobral, Ceará, Brazil). Samples were obtained to determine the fecal egg count per gram feces according to a previously method described (Oliveira et al, 2009). The data were transformed into log 10 (n + 1), where n is the number of eggs per gram feces, and analyzed using the mixed model procedure of the SAS program (2002/2003).…”
Section: Experimental Animals and Phenotypementioning
confidence: 99%